Beneath the Surface: The Decline in Gender Injury Gap - Tiziano Razzolini; Roberto Leombruni; Giovanni Mastrobuoni; Mario Pagliero (Institute for the Study of Labor (IZA), 2013)
Despite its policy relevance there is little evidence on the joint evolution of gender differences in wages and workplace safety. Between 1994 and 2002 Italian micro-level data show a decline in both gaps, as well as an increased concentration of injuries among low-skilled female workers. The reduction in the gender wage gap is driven by sorting of workers across sectors and occupations, while the reduction in the gender injury gap and the increased concentration of injuries among low skilled female workers appears to be driven by changes in unobservables characteristics. Moreover, our findings indicate that in 2002 women became more vulnerable to non-employment spells, which seems to be followed by both wage reductions and increased workplace risk for the re-employed low-skilled female workers.
Keywords: J16; J28; J31; 330; gender gap; workplace injury; job amenities; wage differentials